Sesquiterpene Lactones as Promising Anti-Glioblastoma Drug Candidates Exerting Complex Effects on Glioblastoma Cell Viability and Proneural–Mesenchymal Transition - Andrey V. Markov; Arseny D. Moralev; Kirill V. Odarenko (Biomedicines)
Glioblastoma is one of the most aggressive brain cancers, characterized by active infiltrative growth and high resistance to radiotherapy and chemotherapy. Sesquiterpene triterpenoids (STLs) and their semi-synthetic analogs are considered as a promising source of novel anti-tumor agents due to their low systemic toxicity and multi-target pharmacological effects on key processes associated with tumor progression. The current review aims to systematize the knowledge on the anti-glioblastoma potential of STLs accumulated over the last decade and to identify key processes in glioblastoma cells that are most susceptible to the action of STLs. An analysis of published data clearly demonstrated that STLs, which can successfully cross the blood–brain barrier, exert a complex inhibitory effect on glioblastoma cells through the induction of the “mitochondrial dysfunction–oxidative stress–apoptosis” axis, the inhibition of glucose metabolism and cell cycle phase transition, and the suppression of glioblastoma cell motility and invasion through the blockade of proneural–mesenchymal transition. Taken together, this review highlights the promising anti-glioblastoma potential of STLs, which are not only able to induce glioblastoma cell death, but also effectively affect their diffusive spread, and suggests the possible directions for further investigation of STLs in the context of glioblastoma to better understand their mechanism of action.